EQUATION OF MOTION OF FLOWS WITH SUSPENDED PARTICLES - Гнатів, Ігор (SWorldJournal, 2025)
Recently, it has been increasingly confirmed that the transport of suspended particles is a vital function for the regional and global carbon and nutrient cycle during their transport in surface waters. Usually they include fine sand, silt and clay, which